Creative Tourists in Rural Regions: How do they behave regarding to creative experiences? - Araújo, M.; Pereira, H.; Marques, C. (European Marketing Academy Conference - EMAC 2017, 2017)
This study aims to better understand creative tourists by the identification of tourists’ typologies according to their attitudes and creative experiences they look for in the rural areas. Creative Tourism is a new segment of tourism that offers active and participative tourist products and services that are more interactive to their tastes and personalities. With this purpose, a questionnaire was applied to usual tourists of a Portuguese rural region and a sample of 186 was obtained. Statistical analysis was conducted and 6 clusters, depending on how people understand creativity, was obtained. A contribution of this study is the development of a deeper understanding regarding creative tourists when choosing a rural region, bearing in mind the importance of having a diversified portfolio of experiences. These theoretical implications are relevant both for tourism marketing research and are particular important since this area has recently undergone major developments.